2017
DOI: 10.3390/ma10070769
|View full text |Cite
|
Sign up to set email alerts
|

Study of Adsorption and Desorption Performances of Zr-Based Metal–Organic Frameworks Using Paper Spray Mass Spectrometry

Abstract: The dynamic pore systems and high surface areas of flexible metal–organic framework materials make them excellent candidates to be used in different kinds of adsorption processes. However, the adsorption and desorption behaviors of therapeutic drugs on metal–organic frameworks in solution are not fully developed. Here, we systematically investigated the adsorption and desorption behaviors of a typical therapeutic drug, verapamil, over several Zr-based metal–organic frameworks [e.g., Zr-FUM, UiO-66(Zr), UiO-66(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The chosen material is suspended into an aqueous starch solution, sonicated, possibly heated to boiling (Wang et al, ), and then added to the Buchner funnel containing a filter paper. Coating materials of silica particles (Wang et al, ), metal organic frameworks (MOFs) (Wang et al, ; Dhummakupt et al, ), metal oxides (Zheng et al, ,b), and polystyrene (Wang et al, ; Li et al, ) were studied. Silica particles were observed to fill pores and rest on the paper surface, adhered by the starch (Zheng et al, ).…”
Section: Direct Analysis Of Molecules In Native Statementioning
confidence: 99%
See 1 more Smart Citation
“…The chosen material is suspended into an aqueous starch solution, sonicated, possibly heated to boiling (Wang et al, ), and then added to the Buchner funnel containing a filter paper. Coating materials of silica particles (Wang et al, ), metal organic frameworks (MOFs) (Wang et al, ; Dhummakupt et al, ), metal oxides (Zheng et al, ,b), and polystyrene (Wang et al, ; Li et al, ) were studied. Silica particles were observed to fill pores and rest on the paper surface, adhered by the starch (Zheng et al, ).…”
Section: Direct Analysis Of Molecules In Native Statementioning
confidence: 99%
“…Zirconium‐ and aluminum‐based MOF were vacuum‐coated onto paper to extract drugs from DBSs (Wang et al, ). Results showed that MOF contributed to a matrix suppression effect and a weaker interaction between analyte and the MOF surface compared to the normal analyte‐paper interaction, increasing the sensitivity of verapamil detection in DBSs 3.5–7.8‐fold.…”
Section: Direct Analysis Of Molecules In Native Statementioning
confidence: 99%
“…Phosphonate coordination networks are fast gaining an essential position amongst the families of CNs materials. To expand the adsorption capacity of CNs in a quite large range of pH, it is suggested to choose CNs which are stable in water media [5]. Compared with other adsorbent materials, the main advantages of MOFs and CNs in adsorption processes are their large specific surface area, well ordered unique structures, stable and homogeneous pores of specific sizes.…”
Section: Introductionmentioning
confidence: 99%
“…More relevantly, explosives, herbicides from aqueous matrices, pesticides, and CWA simulants from biofluids have been shown to be effectively analyzed via paper spray mass spectrometry (PS‐MS). The spray substrate has been subjected to a multitude of modifications including the addition of metal–organic‐frameworks (MOFs), carbon nanotubes, silica, urea, silanes, molecularly imprinted polymer (MIPs), and wax printing, with each resulting in a specialized system catering to a specific matrix or target chemistry. For example, these innovative modifications have allowed for sub‐parts‐per‐trillion detections of therapeutic drugs .…”
Section: Introductionmentioning
confidence: 99%